Enhancing the Handover Algorithm with an Intelligent Approach in the O-RAN Architecture - Vilhena, Kleber; Rocha, Carlos; Veiga, Rafael; Bastos, Lucas; Cerqueira, Eduardo; Rosário, Denis (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS), 2024)
O-RAN is an architecture that promotes interoperability and openness in 5G Radio Access Networks (RAN) using scheduling, disaggregation, and virtualization. RICs (RAN Intelligence Controllers) offer solutions such as Machine Learning (ML), traffic steering, anomaly detection, and QoS (Quality of Service) support. Novel intelligent handover strategies are critical to the success of 5G or even 6G O-RAN-based networks. This paper proposes and evaluates an intelligent handover algorithm for O-RAN environments. It leverages an LTE testbed featuring O-RAN architecture to assess downlink and uplink performance across various User Equipment (UE) scenarios. The proposed scheme was implemented and tested using ns-O-RAN, an O-RAN system integrated with the NS-3 simulator. Our simulator results demonstrate a throughput and delay enhancement compared to traditional handover methods across various scenarios involving 50 to 100 UEs.